Les orateurs de « La Pléiade » à l'Académie du Palais (1576) : étude d'un album manuscrit ayant appartenu à Marguerite de Valois - Rouget, François (Renaissance and Reformation / Renaissance et Réforme, 2008)
According to contemporary observers, in the years from 1576 to 1579 Henry III brought together groups of orators-men and women, poets and courtiers-to discuss questions of moral philosophy. This happened both in Paris, and in provincial towns such as Blois and Ollainville. Several of the speeches given by these diverse orators remain extant. Among the spectators was Marguerite de Valois, who ordered the transcription of thirteen speeches that were pronounced during the January-February period of 1576. This album, preserved in a beautifully-bound manuscript, provides an interesting testimony to the intellectual curiosity of Marguerite and to the abiding interest of the king and his court in the domain of eloquence. The present article describes the context in which Marguerite de Valois participated in the first sessions of the Palace Academy, and presents the manuscript volume containing several, palpable traces of her reading of the texts. It also evaluates the contribution of some poets from Marguerite's entourage, such as Ronsard, Desportes, Baïf and Jamyn, and examines aspects of their philosophical debates as well as their oratorical skills.